Occult Hepatitis B Infection among Hemodialysis Patients in Tabriz, Northwest of Iran: Prevalence and Mutations within the S Region - Narges Eslami; Vahdat Poortahmasebi; Javid Sadeghi; Reza Ghotaslou; Bahram Niknafs; Hossein Bannazadeh Baghi; Mahin Ahangar Oskouee (Canadian Journal of Infectious Diseases and Medical Microbiology)
Regardless of the extensive screening for the detection of hepatitis B surface antigen (HBsAg), hemodialysis (HD) patients are still severely at the risk of occult hepatitis B virus infection (OBI), especially in developing countries. OBI is defined as the presence of HBV DNA with undetectable HBsAg in the liver and/or Serum. This study aims to determine the prevalence of OBI in HD patients in East Azerbaijan Province, northwest of Iran, and inquire about the mutations in the detected HBsAg. In this cross-sectional descriptive study, ELISA method assessed serum and plasma samples of 118 HBsAg-negative patients undergoing HD treatment for HBV serological markers (HBsAg and Anti-HBc). Specific primers by nested polymerase chain reaction have been utilized to examine HBV DNA; also, direct sequencing of surface genes was carried out to characterize the viral genotypes and S gene mutations. Finally, followed by real-time PCR, the quantity of viral load in OBI-positive patients was determined. A total of 118 HD patients were included (63.6% were male and 36.4% female), with an overall mean age of 60.8 ± 12.8 years old. The prevalence of antihepatitis B core antibody (Anti-HBc) in the study population was 26.3% (31/118). Five patients (4.2%) were positive for HBV DNA and labeled OBI-positive; their plasma HBV-DNA load was less than 100 IU/ml. Following the phylogenetic analysis, the samples with OBI roughly belonged to genotype D, subtype ayw2 and only two had mutations within the S ’gene’s major hydrophilic region (MHR), including T123I, C124F, and P127T. This study reports the prevalence of OBI in the HBsAg-negative HD patients being at a rate of 4.2%, which can be a clinically vital consideration in this region. HBV serologic screening approaches need to be renewed to cover nucleic acid testing in the setting of hemodialysis and all the other high-risk groups associated with it (i.e., blood and organ donors).